2018
DOI: 10.3389/fvets.2018.00220
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Tonsil Microbiome in Pigs and Effects of Stress on the Microbiome

Abstract: Tonsils, lympho-epithelial tissues located at the junction of the oropharynx and nasopharynx, play a key role in surveillance, colonization, and persistence of inhaled and ingested pathogens. In pigs, the tonsils are a reservoir for numerous bacteria and viruses, including host-specific pathogens and potential zoonotic pathogens as well as commensal organisms. However, there are no in depth studies of the development of the tonsillar microbiome in pigs, or any mammal, over time. The goal of this study was to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…For example, on day 20 during the suckling period, the R. nasisuis inoculated litters housed with sows A and B showed differences in the relative abundance of Moraxella plurianimalium and Veillonella spp. In agreement with a previous study (Pena Cortes et al, 2018) changes in microbiota composition were observed during the transition from suckling to weaning. For example, comparing day 20 (suckling period) with day 35 (8 days after weaning) shows decreased relative abundance of Fusobacterium gastrosuis and an increase in Streptococcus porcorum (Fig.…”
Section: Differential Cytotoxicity Of Valinomycin For Epithelial Cellsupporting
confidence: 93%
See 1 more Smart Citation
“…For example, on day 20 during the suckling period, the R. nasisuis inoculated litters housed with sows A and B showed differences in the relative abundance of Moraxella plurianimalium and Veillonella spp. In agreement with a previous study (Pena Cortes et al, 2018) changes in microbiota composition were observed during the transition from suckling to weaning. For example, comparing day 20 (suckling period) with day 35 (8 days after weaning) shows decreased relative abundance of Fusobacterium gastrosuis and an increase in Streptococcus porcorum (Fig.…”
Section: Differential Cytotoxicity Of Valinomycin For Epithelial Cellsupporting
confidence: 93%
“…As Rothia species are frequently identi ed in porcine oral microbiota (Murase et al;Pena Cortes et al, 2018) we investigated whether valinomycin-producing Rothia strains were present in tonsil swabs of piglets using PCR. We designed one PCR primer set (FLANK) to amplify a genomic DNA region spanning the vlm cluster and upstream region, and a second set of primers (INT) to generate an amplicon within the vlm cluster (Fig.…”
Section: Valinomycin-positive Strains Of Rothia and Valinomycin Are Dmentioning
confidence: 99%
“…It is difficult to compare the core genera across studies. Besides age, commonly studies are done in pigs around weaning [ 45 , 46 ], housing and diet may also impact core genera. Moreover, it has been recently determined that when defining the core microbiome in pigs, differences in study protocols have a significant impact and standardization of experimental techniques appear to be important [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Major microbial shifts occur in response to the transition to solid-feed in the gut microbiome of healthy suckling piglets [22]. This holds true also for the URT microbiome, as weaning has been associated with an increase in the relative abundance of Streptococcaceae and a decrease of Moraxellaceae abundance; this might be result of changes in feed, but also in housing conditions and antimicrobial exposure [18,23]. Feeding strategies and the flooring system have been proposed to impact the composition of the URT respiratory microbiome [24,25].…”
Section: Initial Colonization and Development Of The Respiratory Tracmentioning
confidence: 99%